Caffeine improves performance in double poling during acute exposure to 2,000-m altitude - Stadheim, H. K.; Nossum, E. M.; Olsen, R.; Spencer, M.; Jensen, J. (Journal of Applied Physiology, 2015)
There is limited research on the physiological effects of caffeine (CAF) ingestion on exercise performance during acute hypoxia. The aim of the present study was therefore to test the effect of placebo (PLA) and CAF (4.5 mg/kg) on double poling (DP) performance during acute hypoxia. Thirteen male subelite cross-country skiers (VO2max 72.6 ± 5.68 ml/kg·min) were included. Performance was assessed as 1) an 8-km cross-country DP time-trial (C-PT), and 2) time until task failure at a set workload equal to ~90% of DP V?o2max. Testing was carried out in a hypobaric chamber, at 800 mbar (Pio2: ~125 mmHg) corresponding to ~2,000 m above sea level in a randomized double-blinded, placebo-controlled, cross-over design. CAF improved time to task failure from 6.10 ± 1.40 to 7.22 ± 1.30 min (P < 0.05) and velocity the first 4 km (P < 0.05) but not overall time usage for the 8-km C-PT. During submaximal exercise subjects reported lower pain in arms and rate of perceived exertion (RPE) following CAF ingestion. Throughout C-PTs similar RPE and pain was shown between treatments. However, higher heart rate was observed during the CAF 8 km (187 ± 7 vs. 185 ± 7; P < 0.05) and 90% C-PT (185 ± 7 vs. 181 ± 9) associated with increased ventilation, blood lactate, glucose, adrenaline, decreased pH, and bicarbonate. The present study demonstrates for the first time that CAF ingestion improves DP time to task failure although not consistently time trial performance during acute exposure to altitude. Mechanisms underpinning improvements seem related to reduced pain RPE and increased heart rate during CAF C-PTs.